2015
DOI: 10.1590/s1516-89132015060263
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antimicrobial Assay of Actinomycetes in Rice AgainstXanthomonas oryzae pv. oryzicola and as Potential Plant Growth Promoter

Abstract: The aim of this work was to in vitro assay the antimicrobial activity of actinomycetes in rice against

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…This is comparable to that of Pseudomonas fluorescens CHAO, an IAA hyperproducing strain (195 mg/L) [31]. The strain produced much higher levels of IAA than those reported for bacterial strains reported by various authors such as Hata, et al [7], Khamna, et al [32], Shrivastava, et al [33], Harikrishna, et al [34] and Jog, et al [35]. However, the optimal conditions for IAA production differ among various bacterial strains.…”
Section: Crj2-11 Sugarsupporting
confidence: 76%
See 2 more Smart Citations
“…This is comparable to that of Pseudomonas fluorescens CHAO, an IAA hyperproducing strain (195 mg/L) [31]. The strain produced much higher levels of IAA than those reported for bacterial strains reported by various authors such as Hata, et al [7], Khamna, et al [32], Shrivastava, et al [33], Harikrishna, et al [34] and Jog, et al [35]. However, the optimal conditions for IAA production differ among various bacterial strains.…”
Section: Crj2-11 Sugarsupporting
confidence: 76%
“…However, the optimal conditions for IAA production differ among various bacterial strains. For example, Jog, et al [6], Hata, et al [7], and Ghosh, et al [36] found maximal IAA production in media supplemented with 0.2% trp whereas Jog, et al [35] reported maximal IAA production at 0.5% trp concentration. In contrast, CRJ2-11 produced maximal IAA at 0.8% trp concentration.…”
Section: Crj2-11 Sugarmentioning
confidence: 99%
See 1 more Smart Citation
“…Two Streptomyces strains, S. shenzhenensis TKSC3 (TKSC3) and Streptomyces sp. SS8 (SS8) were selected based on a previous study ( Hata et al, 2015 ). TKSC3 and SS8 16S rDNA sequences have been deposited in the GenBank database with accession numbers KP792984 and KP792988, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the total carbohydrate contents of both cell fractionations were determined by using the total carbohydrate colorimetric assay kit (Milpitas, CA 95035 USA). The nitrate reductase enzyme in both cell fractionations was checked and assayed according to 29 , 31 , 52 . Cell fractionations were mixed with 10 ml of assay medium (30 mM KNO 3 and 5% isopropanol in 0.1 M phosphate buffer of pH 7.5) and incubated at 30 °C for 1 hr in the dark condition.…”
Section: Methodsmentioning
confidence: 99%